Peran Supervisi Akademik dalam Meningkatkan Mutu Pembelajaran di SMK YLA Cibadak - Yuyu Yuhaeni; Siti Qomariyah; Ujang Ruslandi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Academic supervision plays a strategic role in ensuring the quality of learning in educational institutions, including at YLA Cibadak Vocational School. This research aims to explore the role of academic supervision in improving the quality of learning through a collaboration-oriented approach, developing teacher competence, and pedagogical innovation. Using descriptive qualitative research methods, data was obtained through observation, in-depth interviews, and analysis of supervision documents. The research results show that effective academic supervision not only functions as an evaluation tool, but also as a medium for educational transformation that involves teachers as strategic partners. The main findings underline the importance of two-way communication patterns, preparing needs-based follow-up plans, and empowering teachers through ongoing training and mentoring. This research recommends a supervision model based on empathy and local contextualization that is able to answer the unique needs of SMK YLA Cibadak, as well as being an inspiration for other institutions. With this approach, academic supervision can be a driving force in creating a dynamic, adaptive and quality-oriented learning ecosystem.